Good Worker Health and Hygiene Practices: Training Manual for Produce Handlers - Amy Simonne; Jeffrey Brecht; Steve Sargent; Mark Ritenour; Keith Schneider (EDIS, 2005)
The goal of this first Edition of Good Worker Health and Hygiene Practices: Training Manual for Produce Handlers is to provide owners, managers, and/or supervisors in Florida's produce industry a training tool for their workers. Drawn from many sources in the subject area including the FDA-GAPs, FDA-GMPs, FDA Model Food Code, recommendations from the American College of Occupational and Environmental Medicine, and other publications from federal government agencies, this manual is designed to be a reference to accompany the other educational materials included in the UF/IFAS Worker Health and Hygiene Training Program.  This document is FCS8769, one of a series of the Family, Youth and Community Sciences Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Original publication date May 9, 2005.